LINGUISTIC TYPOLOGY - Saloxiddinov Manuchehr; Rabbimov Oybek (International Engineering Journal For Research & Development, 2022)
Typology is derived term of word “type”. As nouns the difference between typology and type is that typology is the systematic classification of the types of something according to their common characteristics while type is a grouping based on shared characteristics. Before reviewing typology examples, it's important to really understand the definition of typology. Understanding what typology is will make it easier to understand how certain examples illustrate the concept. A typology is simply a means of classifying items, people or concepts by general type. The word typology is simply a scientific term for grouping things together based on similarities. A typology of the field of study includes numerous categories like applied, archaeological, biological, cultural, forensic, and linguistic one.